Fabrication of drug eluting implants: study of drug release mechanism from titanium dioxide nanotubes. (10th June 2015) - Hamlekhan, Azhang; Sinha-Ray, Suman; Takoudis, Christos; Mathew, Mathew T; Sukotjo, Cortino; Yarin, Alexander L; Shokuhfar, Tolou
Abstract: Formation of titanium dioxide nanotubes (TNTs) on a titanium surface holds great potential for promoting desirable cellular response. However, prolongation of drug release from these nano-reservoirs remains to be a challenge. In our previous work TNTs were successfully loaded with a drug. In this study the effect of TNTs dimensions on prolongation of drug release is quantified aiming at the introduction of a simple novel technique which overcomes complications of previously introduced methods. Different groups of TNTs with different lengths and diameters are fabricated. Samples are loaded with a model drug and rate of drug release over time is monitored. The relation of the drug release rate to the TNT dimensions (diameter, length, aspect ratio and volume) is established. The results show that an increase in any of these parameters increases the duration of the release process. However, the strongest parameter affecting the drug release is the aspect ratio. In fact, TNTs with higher aspect ratios release drug slower. It is revealed that drug release from TNT is a diffusion-limited process. Assuming that diffusion of drug in (Phosphate-Buffered Saline) PBS follows one-dimensional Fick's law, the theoretical predictions for drug release profile is compatible with our experimental data for release from a single TNT.